2018
DOI: 10.1038/s41467-018-05853-7
|View full text |Cite|
|
Sign up to set email alerts
|

Factors of the bone marrow microniche that support human plasma cell survival and immunoglobulin secretion

Abstract: Human antibody-secreting cells (ASC) in peripheral blood are found after vaccination or infection but rapidly apoptose unless they migrate to the bone marrow (BM). Yet, elements of the BM microenvironment required to sustain long-lived plasma cells (LLPC) remain elusive. Here, we identify BM factors that maintain human ASC > 50 days in vitro. The critical components of the cell-free in vitro BM mimic consist of products from primary BM mesenchymal stromal cells (MSC), a proliferation-inducing ligand (APRIL), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
153
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(159 citation statements)
references
References 57 publications
4
153
0
Order By: Relevance
“…178,[180][181][182][183][184] The necessity of some of these cell types and secreted cytokines has been disputed, but a common proposed feature of these populations is their ability to secrete pro-survival cytokines and in turn support plasma cell longevity. 190 Culturing these cells under physiological oxygen tension and with MSC supernatants further enhanced survival, suggesting an as yet unexplored role for hypoxia in plasma cell survival. Human plasma cells co-cultured with primary mesenchymal stromal cells (MSCs) survived in in vitro cultures for up to 8 weeks, vs those cultured in media alone, that died within one day.…”
Section: Cell Extrinsic Factorsmentioning
confidence: 98%
See 3 more Smart Citations
“…178,[180][181][182][183][184] The necessity of some of these cell types and secreted cytokines has been disputed, but a common proposed feature of these populations is their ability to secrete pro-survival cytokines and in turn support plasma cell longevity. 190 Culturing these cells under physiological oxygen tension and with MSC supernatants further enhanced survival, suggesting an as yet unexplored role for hypoxia in plasma cell survival. Human plasma cells co-cultured with primary mesenchymal stromal cells (MSCs) survived in in vitro cultures for up to 8 weeks, vs those cultured in media alone, that died within one day.…”
Section: Cell Extrinsic Factorsmentioning
confidence: 98%
“…133,179 A number of accessory cell types such as eosinophils, basophils, megakaryocytes, regulatory T cells, and mesenchymal cells have all been proposed to enhance plasma cell survival. 190 Functional secretome analyses revealed that fibronectin-1 and the 14-3-3 zeta/delta proteins promote plasma cell survival, suggesting a role for the extracellular matrix proteins. [185][186][187][188][189] The integration of these signals with primary plasma cell metabolism, however, has been understudied with a notable recent exception.…”
Section: Cell Extrinsic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct ASC interrogation can be enhanced by recent improvements in the ability to maintain the survival of PB in vitro for several weeks. 59 In turn, in vitro stimulation leading to antibody production can be applied to multiple B-cell populations including transitional, naive, memory, and effector DN B-cells using different activation conditions. 52,60-65 Similar protocols can be applied to ELISPOT detection to obtain a more quantitative measurement at Nevertheless, single-cell cultures afford the ability to test antibodies against multiple antigens (including the use of large antigens arrays) while also providing mRNA for the generation of mAbs derived from the cells of interest for both validation and additional testing and applications.…”
Section: Autoreactivity Measurementsmentioning
confidence: 99%